KARAKTER DAN PERIODISASI DALAM FILSAFAT - Akhmad Nurul Kawakib (lp2m-uin malang, 2014)
Oleh:Akhmad Nurul KawakibFakultas Ilmu Tarbiyah dan Keguruan, UIN Maulana Malik Ibrahim Malang Email: kawakib.akhmad@gmail.com Abstract This paper identifies the characteristic of modern and contemporary of philosophy. Modern philosophy is dominated by a concern with the epistemological issues, while the contemporary analytic philosophy represents a shift to issues a logical-linguistic sort. The study of modern Philosophy also identifies the power of mind and the efforts to achieve external world and to obtain the structure of reality. The problem is not to understand whether it is possible to achieve knowledge. The problem is to show the ways in which this comes about, the conditions and procedures for achieving such knowledge. It is also important to note that the conception of reality is best understood as equivalent in meaning to the concept of the truth. To say what reality is requires that there be a saying, a belief that is arrived at a result of investigation.